Queer Migration Politics: Activist Rhetoric and Coalitional Possibilities - Chavez, Karma (feminists@law, 2013)
Karma Chavez's forthcoming book, Queer Migration Politics, suggests that neither the inclusionary politics of the mainstream US LGBT rights movement nor the utopian turn in some queer theory sufficiently capture the possibilities for queer politics in this moment. Drawing on the rhetoric of activists working at the various intersections and convergences of queer and immigration rights and justice, Chávez advocates that coalition is a productive alternative to both inclusionary and utopian approaches, even as coalitional approaches sometimes draw upon them both. In this talk, Chavez sketches the main arguments in the book and discusses some of the key case studies from activist rhetoric in the contemporary United States. A podcast of the lecture can also be found on the Decolonizing Sexualitie Network website at http://www.decolonizingsexualities.org/karma-chavez-lecture/.